Status of Eunuchs in India - Brat Dash, Sidhya; Pattnaik, Sibasis (International Journal of Psychosocial Rehabilitation, 2025)
The landmark judgement of NALSA vs Union of India recognised the various civil rights of transgender community. This paper attempt to explore the various dimensions of the eunuch’s community, by discussing about their history, social recognition, legal status etc. This paper attempt to shed light on the status of transgender in India, the background of the court in understanding and recognising the status of eunuchs within the preview of Indian society and acknowledgement of their rights